STRATEGI PENGEMBANGAN PADA SENTRA USAHA TAUGE DI DESA HULAAN, KECAMATAN MENGANTI, KABUPATEN GRESIK - administrator, administrator; Saputra, Ramadhan; Humaidi, Faisol (Fakultas Pertanian Universitas Wijaya Putra, 2023)
This study aims to identify the strengths, weaknesses, opportunities and threats in theprocess of developing bean sprouts business centers, as well as determine the strategy fordeveloping the bean sprouts business in Hulaan Village, Menganti District, GresikRegency. The analytical method used in this research is descriptive analysis and SWOTanalysis. The sampling technique used in this study used a purposive sampling technique.The sample was taken by 16 people from bean sprout business owners in Hulaan Village,Menganti District, Gresik Regency. From the results of identification that has been carriedout from the internal factors of strengths and weaknesses, 12 aspects have been found, andfrom external factors, opportunities and threats have been found to be 7 aspects that willbe related to the strategy for developing bean sprouts business centers. This study showsthat the strategic position of the development of the bean sprouts business center in HulaanVillage, Menganti District, Gresik Regency is in quadrant I, which means that the beansprouts business center in Hulaan Village has internal strength in its development. Fromthe results of the analysis that has been carried out, as a strategy recommendation given isan Aggressive strategy, meaning maximizing strengths and taking advantage of existingopportunities to get the bean sprouts business development strategy implemented.